Beban Kerja dan Kelelahan Kerja pada Perawat di Ruang Rawat Inap RSUD Prof. Dr. W. Z. Johannes Kupang - Egla Taruk Lembang; Andreas Umbu Roga; Marylin Susanti Junias (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Heavy workload requires a nurse to be able to carry out nursing care properly. shift work can cause nurse fatigue due to lack of sleep and inadequate recovery time between shifts. Work fatigue is one of the risks that affect performance decline which can increase the error rate at work. The purpose of this study was to determine the relationship between workload and work shifts with work fatigue in nurses in the Inpatient Room of RSUD Prof. Dr. W. Z.  Johannes Kupang in 2023. This type of research is an analytic observational using a cross sectional design. The population in this study were nurses who served in the inpatient room of Prof. Dr. W. Z. Hospital. Johannes in 2023 with a sample of 66 nurses. Sampling using is simple random sampling. Data analysis used was univariate analysis and bivariate analysis with chi-square statistical test. Based on statistical tests, it was found that there was a significant relationship between workload and fatigue (p = 0.004) and work shifts with fatigue (p = 0.014) at RSUD Prof. Dr. W. Z. Johannes Kupang in 2023. It is recommended for hospitals to distribute nurses and organize shift rotations properly, so as to produce more effective work productivity in providing health services